FEATURES OF THE DEVELOPMENT OF STARTUPS IN THE IT INDUSTRY - Kapiton, Alla; Skakalina, Olena; Sas, Nataliia; Mostova, Anastasiia; Sokol, Halyna (European Science, 2023)
The article is designed to analyze the problem of developing startups in the IT industry. As a result of the research, it was determined that during the constant growth of demand for modern software development, a large number of various startups are reg